Classical Music Decrease Stress Level And Blood Pressure Primigravida In The Third Trimester - Ni Ketut Alit Armini; Erna Dwi Wahyuni; Praba Diyan Rachmawati (Universitas Airlangga, 2008)
Introduction: Many changes in psychology and biology increase primigravida’s stress in the third trimester. The stress response makes blood pressure being unstable, it causes bad effect for pregnancy. Classical music can be used as one of relaxation facilities that can reduce stress. The aimed of this study were to analyze the effect of classical music on stress level and blood pressure.Methods: This study was used a quasy experimental purposive sampling design. The sample in this study were 14 pregnancy women in the third trimester in RSIA Cempaka Putih Permata Surabaya. The independent variable in this study was classical music and the dependent variable were stress level and blood pressure. Data were analyzed by Wilcoxon Signed Rank Test, Mann Withney U Test, Paired t Test and Independent t Test with significance level α≤0.05.Results: The result showed that the stress level in controlled group with p=0.567 and intervention group with p=0.025. The result of blood pressure in controlled group with p=0.522 in systolic blood pressure, p=0.35 in diastolic blood pressure and intervention group showed p=0.103 in systolic blood pressure and p=1.00 in diastolic blood pressure.Conclusion: It can be concluded that listening classical music can reduce stress level, stabilize blood pressure, although blood pressure hasn’t significant result but mean of blood pressure show that it was stable. Further studies should be considered to used cortisol to identify stress biology response spesifically.